2014
DOI: 10.4103/0970-4388.127039
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status of 5 years and 12 years old school going children in rural Gurgaon, India: An epidemiological study

Abstract: Preventive approaches seem to be a viable alternative to tackle the overwhelming problem of dental caries and other oral diseases. Provision of oral health education in schools and school based preventive programs are important for improvement of this situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 0 publications
4
27
3
Order By: Relevance
“…Yes No children (81.36%) do not practice interdental cleaning habits which is again in contrast with the study done by JayakumariMuttappallymyalil et al in Kerala where 58% practiced interdental cleaning habits [7] In a study done by Navneet Grewal on 100 Indian children, only 35% never visited dentist [8] but in this study only 32.2% visited dentist which is similar to the study done by Zhu L P et al 35.3% 12 years and 20.2% 18 years visited dentist [9] A positive result that was brought out was 34.74% had caries which is in total contrast with the study done by Meenu Mittal et al in Gurgaon on 5 year aged children wherein 68.5% had dental caries [10].…”
Section: Do You Have Cavities?contrasting
confidence: 56%
“…Yes No children (81.36%) do not practice interdental cleaning habits which is again in contrast with the study done by JayakumariMuttappallymyalil et al in Kerala where 58% practiced interdental cleaning habits [7] In a study done by Navneet Grewal on 100 Indian children, only 35% never visited dentist [8] but in this study only 32.2% visited dentist which is similar to the study done by Zhu L P et al 35.3% 12 years and 20.2% 18 years visited dentist [9] A positive result that was brought out was 34.74% had caries which is in total contrast with the study done by Meenu Mittal et al in Gurgaon on 5 year aged children wherein 68.5% had dental caries [10].…”
Section: Do You Have Cavities?contrasting
confidence: 56%
“…[10][11][12] Mittal et al found that, among the 5 year group prevalence of dental caries was 69.4% in males and 67.62% in females and among the 12 year age group, caries prevalence of caries was 41% in males and 33% in females. 19 Contrastingly a study by Rajesh et al the prevalence of dental caries was found to be almost equal among the female (34%) and male (31.8%) students and Ahmed et al reported that there was no difference in the prevalence of dental caries between males (30.7%) and females (31%) and this discrepancy can be attributed to different age groups. 13,20 …”
Section: Gendercontrasting
confidence: 45%
“…Among oral diseases, the dental caries[34] is an important dental public problem in India and is predominantly a disease of childhood. Pain due to dental caries can affect normal food intake and daily curriculum and sports activities in the children.…”
mentioning
confidence: 99%